Genome-wide signatures of complex introgression and adaptive evolution in the big cats - Figueiró, Henrique V. (2017)
The great cats of genus Panthera are amongst the most iconic animals in the world, capturing historical human fascination and present concern regarding their imperilled status in the wild. The five extant species derive from a recent radiation, which has posed difficulties to the resolution of their phylogeny, while offering opportunities to understand the adaptive divergence of closely related and widely successful top predators. Here we report the sequence, de novo assembly and annotation of the jaguar (Panthera onca) genome, and comparative analyses with all other Panthera species, including novel genomic data from the leopard. We observed pervasive genealogical discordance across the Panthera genomes, caused by both incomplete lineage sorting and complex patterns of historical interspecific hybridization. Introgressed genomic segments include loci bearing signatures of selective sweeps, suggesting that post-speciation admixture facilitated the evolutionary rescue of lineages affected by small and/or unstable effective population sizes. We used site-based models and genome-wide timetree scans to identify signatures of positive selection in the Panthera genomes, affecting genes involved in brain, skull and limb development, body size, sensory perception, pigmentation and behaviour. These findings reveal the complex history of the Panthera radiation and several genes that may underlie its current phenotypic diversity.